Positive Thinking during Covid-19 Pandemic - Fat Chiya Nidaul Chusna; Wiwien Dinar Pratisti (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
The Covid-19 pandemic entered Indonesia in early 2020 and has not ended until now. The pandemic not only causes a wide impact on health problems, but also social, economic, educational, and psychological problems. One of them is the stress that occurs in society. One way to deal with stress is to think positively. The purpose of this scientific article is to find out positive thinking and its implications for reducing stress. The method used in this paper is a literature review. The results obtained are positive thinking can help overcome and reduce stress in the environment of health workers, social circles, as well as the environment for adolescents and students.